2002
DOI: 10.1007/s00125-002-0915-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and the occurrence of ventricular arrhythmic events in patients with severe left ventricular dysfunction

Abstract: Aims/hypothesis. Diabetes is associated with a higher risk of ischaemic heart disease and heart failure, which frequently lead to rhythm disorders. However, experimental and clinical studies are inconsistent with regard to the risk of arrhythmic events in patients with diabetes. We studied the frequency of ventricular arrhythmic events in patients with and without diabetes. Methods. The study group included 207 patients with severe heart failure. The severity of ventricular arrhythmias was assessed by 24-h Hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(28 reference statements)
2
5
0
Order By: Relevance
“…Information concerning prevalence and impact on survival of various clinical variables in the context of DM and established CHF is limited [2,10,11,12,13, 17, 18]. Our results confirm that survival is shortened in diabetics with CHF.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Information concerning prevalence and impact on survival of various clinical variables in the context of DM and established CHF is limited [2,10,11,12,13, 17, 18]. Our results confirm that survival is shortened in diabetics with CHF.…”
Section: Discussionsupporting
confidence: 79%
“…pulmonary edema on admission [2], anemia, cardiac conduction disturbances, hyponatremia, use of nitrates [12] and higher long-term furosemide dosages, significantly prevailed in this subgroup. RD [11, 13] and peripheral vascular disease [11] also prevailed in the DM subgroup, but did not reach statistical significance. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, another study investigating the asso ciation between diabetes and VA in patients with severe heart failure revealed a negative independent relationship with diabetes and VA in this patient group. Moreover, the authors concluded that DM might have a protective effect for the occurrence of VA in the setting of decompensated heart failure [37] . In summary, DM might play a critical role in creating a vulnerable substrate and/or as a trigger for VA besides the expected risk based on the high extent and incidence of coronary artery disease.…”
Section: Diabetes and Ventricular Arrhythmiasmentioning
confidence: 99%